ANALYSIS OF STUDENT ABILITY IN FUNCTIONAL THINKING THROUGH THE FUNCTION TABLE: THE CASE OF SQUARE FUNCTION - Suci Yuniati; Suparjono Suparjono; Annisah Kurniati (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
One way to track students' ability to understand the concept of function can be done by analyzing their functional thinking skills. This study aims to identify and determine students' functional thinking skills through function tables. This research is an exploratory qualitative research. The research subjects were 2 out of 56 5th semester students of the Department of Mathematics Education, Suska Riau State Islamic University. The research subjects were selected purposively, namely students who correctly completed the test sheet and had fluent communication skills. Data were collected through tests and interviews. The results of the test answer sheets were analyzed based on the functional thinking framework and the results of the interviews were analyzed to explore and clarify students' functional thinking that had not been revealed on the answer sheets. The results of data analysis show that there are two stages of completion, namely the first stage, determining the number pattern and thinking about the number pattern up to the nth, determining the difference from , determining the difference from , determining the change in value between and , generalizing the sequence, and generalizing sequence. While the second stage, determine the change in value between and , generalize sequence , generalize sequence , and generalize the relationship between and . Based on the results of the study, it showed that students were able to fulfill all the frameworks for solving problems through the function tableSalah satu cara untuk menelusuri kemampuan mahasiswa dalam memahami konsep fungsi dapat dilakukan dengan cara menganalisis kemampuan berpikir fungsionalnnya. Penelitian ini bertujuan untuk mengidentifikasi dan mengetahui kemampuan berpikir fungsional mahasiswa melalui tabel fungsi. Penelitian ini merupakan penelitian kualitatif yang bersifat eksploratif. Subjek penelitian adalah 2 dari 56 mahasiswa semester 5 Jurusan Pendidikan Matematika Universitas Islam Negeri Suska Riau. Subjek penelitian dipilih secara purposive yaitu mahasiswa yang menyelesaikan secara benar lembar tes dan memiliki kemampuan komunikasi yang lancar. Data dikumpulkan melalui tes dan wawancara. Hasil lembar jawaban tes dianalisis berdasarkan kerangka kerja berpikir fungsional dan hasil wawancara dianalisis untuk mendalami dan mengklarifikasi berpikir fungsional mahasiswa yang belum terungkap pada lembar jawaban. Hasil analisis data menunjukan bahwa ada dua tahapan penyelesaian yaitu tahap pertama, menentukan pola bilangan dan berpikir tentang pola bilangan sampai ke-n, menentukan beda dari , menentukan beda dari , menentukan perubahan nilai antara dan , menggeneralisasikan barisan , dan menggeneralisasikan barisan . Sedangkan tahap kedua, menentukan perubahan nilai antara dan , menggeneralisasikan barisan , menggeneralisasikan barisan , dan menggeneralisasikan hubungan antara dan . Berdasarkan hasil penelitian menunjukkan bahwa mahasiswa mampu memenuhi semua kerangka kerja berpikir fungsional dalam menyelesaikan masalah melalui tabel fungsi.